Is the Scope of Costs Considered in Budget Impact Analyses for Anticancer Drugs Rational? A Systematic Review and Comparative Study - Ma, Yue; Li, Yuxin; Ma, Aixia; Li, Hongchao (Frontiers in Public Health, 2021)
Background With the increasing disease burden of cancer worldwide, more and more anticancer drugs have been approved in many countries, and the results of budget impact analyses (BIAs) have become important evidence for related reimbursement decisions. Objectives We systematically reviewed whether BIAs for anticancer drugs consider the scope of costs rationally and compared the results of different cost scopes to provide suggestions for future analyses and decision-making. Methods Eligible BIAs published in PubMed, Embase, Web of Science, and the Cochrane Library from 2016 to 2021 were identified based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We extracted 15 terms from the included studies and analyzed how they considered the scope of costs. In addition, a budget impact model was developed for the introduction of geptanolimab to China’s National Reimbursement Drug List to enable a comparison of two cost-scope scenarios. Results A total of 29 studies were included in the systematic review. All 29 studies considered the costs of anticancer drugs, and 25 (86%) also considered condition-related costs, but only 11 (38%) considered subsequent treatment costs. In the comparative study, the predicted budget impacts from 2022 to 2024 were significantly impacted by subsequent treatment costs, with annual differences between the two cost-scope scenarios of 39,546,664, 65,866,161, and 86,577,386, respectively. Conclusions The scope of costs considered in some existing BIAs for anticancer drugs are not rational. The variations between different cost scopes in terms of budget impact were significant. Thus BIAs for anticancer drugs should consider a rational scope of costs that adheres to BIA guidelines. Researchers and decision-makers should pay more attention to the scope of costs to achieve better-quality BIAs for anticancer drugs and enhance reimbursement decision-making.